2016
DOI: 10.1007/s11356-016-6065-y
|View full text |Cite
|
Sign up to set email alerts
|

Removal ratio of gaseous toluene and xylene transported from air to root zone via the stem by indoor plants

Abstract: This work was designed to investigate the removal efficiency as well as the ratios of toluene and xylene transported from air to root zone via the stem and by direct diffusion from the air into the medium. Indoor plants (Schefflera actinophylla and Ficus benghalensis) were placed in a sealed test chamber. Shoot or root zone were sealed with a Teflon bag, and gaseous toluene and xylene were exposed. Removal efficiency of toluene and total xylene (m, p, o) was 13.3 and 7.0 μg·m(-3)·m(-2) leaf area over a 24-h pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…VOCs (Ugrekhelidze et al 1997, Kim and Jeon 2009, Sriprapat and Thiravetyan 2013, Dela Cruz et al 2014, Kim et al 2016, Hörmann et al 2018. However, it is known that the efficiency of VOC removal varies substantially both among plant species (Kim et al 2018, Yoo et al 2006, and with the molecular characteristics of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…VOCs (Ugrekhelidze et al 1997, Kim and Jeon 2009, Sriprapat and Thiravetyan 2013, Dela Cruz et al 2014, Kim et al 2016, Hörmann et al 2018. However, it is known that the efficiency of VOC removal varies substantially both among plant species (Kim et al 2018, Yoo et al 2006, and with the molecular characteristics of individual compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Given the leaf area of all plant species and an initial concentration in the chamber, conversion to CADR p was possible. Kim et al [46] plotted concentration over time for two distinct plant species removing three different VOCs. The CADR p results for these studies are detailed in Table S2.…”
Section: Description Of Considered Chamber Experimentsmentioning
confidence: 99%
“…This figure thus explores the possibility of constraining CADR p for each VOC. Some of the data preliminarily indicates that certain VOCs may be more efficiently removed by potted plants; for instance, Kim et al [44][45][46] observed better formaldehyde removal than for xylene, and Wolverton et al [49] observed a much lower TCE removal than for formaldehyde and benzene. However, these trends are not consistent throughout all studies; for instance, Yang et al [50] observed similar removal of TCE, benzene, and toluene.…”
Section: Cadr Of Potted Plants In Reviewed Studiesmentioning
confidence: 99%
See 2 more Smart Citations